2007
DOI: 10.1097/01.anes.0000264790.07231.2d
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Entropy/Complexity Measures of the Electroencephalogram during Propofol-induced Sedation

Abstract: Cutting off high frequencies from the electroencephalogram and increased remifentanil concentration deteriorate the performance of the electroencephalogram-based entropy/complexity measures as indicators of the depth of propofol sedation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
66
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 27 publications
5
66
0
1
Order By: Relevance
“…Several investigators have compared spectral entropy parameters with BIS using different anesthetic drugs during the period of induction of anesthesia [12][13][14], but their results were inconsistent. In the present study, the comparability of RE and SE, and BIS was investigated during the period of maintenance of the propfol-remifentanil anaesthesia, where the remifentanil concentration was kept constant, and fentanyl was added at expected painful periods.…”
Section: Discussionmentioning
confidence: 99%
“…Several investigators have compared spectral entropy parameters with BIS using different anesthetic drugs during the period of induction of anesthesia [12][13][14], but their results were inconsistent. In the present study, the comparability of RE and SE, and BIS was investigated during the period of maintenance of the propfol-remifentanil anaesthesia, where the remifentanil concentration was kept constant, and fentanyl was added at expected painful periods.…”
Section: Discussionmentioning
confidence: 99%
“…Various commercial and noncommercial depth of anesthesia monitoring approaches have been developed (Kissin, 2000;Struys et al, 2002;Jordan et al, 2006;Ferenets et al, 2007;Liley et al, 2010;Shalbaf et al, 2013;Shoushtarian et al, 2015b,a) that primarily 5 rely on extraction of features from the EEG to track anesthetic brain state. Despite significant history and recent work attempting to characterise the mulit-channel EEG and brain networks related to anesthesia in more detail (Cimenser et al, 2011;Lewis et al, 2012;Purdon et al, 2013;Kuhlmann et al, 2013;Lee et al, 2013), the international uptake of automated depth of anesthesia monitoring in the clinic is still lagging.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore model-based approaches present an interesting alternative to the more standard extraction of EEG features employed in depth of anesthesia monitoring (Kissin, 2000;Jordan et al, 2006;Ferenets et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers have demonstrated that LZC and ApEn can distinguish between awake and anaesthetized state of human subjects (Anderson, Barr, 2004, Bruhn, Bouillon, 2003, Ferenets et al , 2006, Ferenets et al , 2007, Hans, Dewandre, 2005, Kumar et al , 2007, Noh et al , 2006, Vakkuri, Yli-Hankala, 2004, Voss et al , 2006, Zhang, Roy, 2001). In sleep research ApEn was statistically significantly lower during Stage IV and higher during wake and REM sleep (Burioka et al , 2005, Papadelis et al , 2007.…”
Section: Clinical Application Of Nda Correlated With Unconsciousnessmentioning
confidence: 99%